2016
DOI: 10.1177/0734242x16675683
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment of potential municipal solid waste management strategies for Mumbai, India

Abstract: Dumping of municipal solid waste into uncontrolled dumpsites is the most common method of waste disposal in most cities of India. These dumpsites are posing a serious challenge to environmental quality and sustainable development. Mumbai, which generates over 9000 t of municipal solid waste daily, also disposes of most of its waste in open dumps. It is important to analyse the impact of municipal solid waste disposal today and what would be the impact under integrated waste management schemes. In this study, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 30 publications
3
42
1
1
Order By: Relevance
“…Overall, MSWM option A5 emerges as the best option for managing MSW in Harare as shown in Table 6. This is confirmed from findings by Sharma and Chandel [111] that MSWM systems that combines incineration, anaerobic digestion, composting and materials recovery have the least environmental impacts. The recovery of landfill gas for combined heat and power (CHP) generation under the current study is attributed to the reduction of impact potentials across all the impact categories under consideration, except for A4 under acidification, in the MSWM options that incorporated landfilling because energy recovery from waste bring significant environmental benefits [95,110,[112][113][114][115][116].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Overall, MSWM option A5 emerges as the best option for managing MSW in Harare as shown in Table 6. This is confirmed from findings by Sharma and Chandel [111] that MSWM systems that combines incineration, anaerobic digestion, composting and materials recovery have the least environmental impacts. The recovery of landfill gas for combined heat and power (CHP) generation under the current study is attributed to the reduction of impact potentials across all the impact categories under consideration, except for A4 under acidification, in the MSWM options that incorporated landfilling because energy recovery from waste bring significant environmental benefits [95,110,[112][113][114][115][116].…”
Section: Discussionsupporting
confidence: 81%
“…Overall, MSW management option A5 emerges the best option for managing MSW in Harare as shown in Table 6. This is confirmed from findings by Sharma and Chandel [111] that MSW management that combines incineration, anaerobic digestion, composting and materials recovery has the least environmental impacts. Therefore, the LCA results from this study will inform the design and development of future integrated MSWM systems with reduced environmental and human health impacts.…”
Section: Discussionsupporting
confidence: 80%
“…Support should also be provided to research initiatives conducted by academic and research institutions in areas that are related to waste management, environmental sanitation, and personal hygiene by funding them partially or fully. The study conducted by Sharma and Chandel (2017) in M umbai, India has shown that…”
Section: Figure 1: Framework For Ensuring Efficiency In Municipal Solmentioning
confidence: 99%
“…In the Indian context, Sharma and Chandel (2017) compared six different scenarios for MSW management strategies for Mumbai city, India using the LCA approach. The scenarios included landfill with biogas collection, incineration and different combinations of recycling, landfill, composting, anaerobic digestion and incineration.…”
Section: Introductionmentioning
confidence: 99%
“…The economic assessment is performed using methods proposed for process engineering economics (Peters et al, 2003). LCA is a useful method for environmental and human health impact assessment (Finkbeiner et al 2006; Finnveden et al 2009; ISO, 2006a, 2006b) and has been applied for MSW management (Chaya and Gheewala, 2007; Cherubini et al, 2009; Damgaard et al, 2011; De Feo and Malvano, 2009; Khoo, 2009; Manfredi and Christensen, 2009; Sharma and Chandel, 2017; Tan et al, 2015). Therefore, this work uses LCA for environmental and human health impact assessment.…”
Section: Introductionmentioning
confidence: 99%